COLOUR TYPES AND ANALYSIS: SEMANTIC AND STYLISTIC - Bazarbaeva, Albina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The concept of holistic perception of a speech or literary work does not exclude paying attentive attention to its individual elements. Because words are the fundamental unit of language, it is critical to consider their notion and meaning. A word in a language is a polysemantic rule, which implies that it contains several lexicosemantic variants via which it may be understood in one of its meanings. Each individual lexico-semantic variant's lexical meaning is a complex unity.